The Effect of Voltage on HDPE Microplastic Removal by Electrocoagulation Process Using Stainless Steel Electrode - Mei Dian Syaputra; Pranoto Pranoto; Triana Kusumaningsih (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Plastic pollution, especially high-density polyethylene (HDPE), is highly concerned with human health and ecosystems. This study investigates the potential of the electrocoagulation process on the removal of HDPE microplastics from water, evaluating the best operating conditions, including the voltage (4, 8, and 12 V), time (40, 80, and 120 minutes), and pH (3, 5, 7, and 9) to achieve the maximum removal efficiency. Coagulation experiments were conducted in the electrolytic cell, using stainless steel and aluminum electrodes, while Na₂SO₄ served as the electrolyte. Because loss of surface area and change in structure was more evident in fragmented flake and granular microplastics (FTIR and SEM analyses), those microplastics were more retained in the swollen coagulant. The alkaline condition also supports the highest removal efficiency of 96.60% when the pH, voltage, and duration were 9, 8V, and 120 minutes, respectively, as experienced in addition to 0.1g of carbon CTO5 in the study. Conclusions Our findings show that electrocoagulation works best at a medium voltage and in alkaline pH conditions. Under low pH conditions, the removal is not notably influenced by the applied voltage, whereas under neutral and alkaline conditions, removal is significantly enhanced with increased voltage. Moreover, the stainless steel electrodes were more corrosion-resistant than aluminum, thus making the process more sustainable. The results indicate that electrocoagulation represents an environmentally friendly, effective microplastic removal method under the right voltage, time, and pH conditions. Such techniques are an effective strategy that helps reduce water contamination and conserve ecosystems.